Strategic Orientation: Integrating Entrepreneurial, Collective, and Market Orientations to Enhance MSMEs' Performance - Umu Khouroh; Sari Yuniarti; Irany Windhyastiti; Rafiq Firdaus Al-Asjim (Media Ekonomi dan Manajemen, 2024)
MSMEs in Indonesia face fundamental problems in developing business strategies. This research explores the impact of strategic orientation (SO) on business performance. SO involves the integrated role of entrepreneurial orientation (EO), market orientation (MO), and collective orientation (CO) in improving performance. This research also examines the mediating role of CO, MO and the moderating role of EO. Demographic variables are used as control variables. Data obtained from 192 creative industries in Malang Raya with a response rate of 65 percent (124 MSMEs). This study utilizes PLS-SEM methodology to investigate target relationships. The results show that MSME performance is significantly influenced by SO, both EO and MO, but not CO. This confirms the direct influence of EO and MO on performance, as well as the indirect influence of MO on the EO-performance relationship. In addition, this research reveals that the performance of MSMEs managed by women tends to be lower than MSMEs managed by men. This is because the EO characteristics of men are greater than those of women. The implication of these findings is that MSMEs must improve EO and MO. Effective CO needs to be strengthened so that it can make a major contribution to sustainability of MSMEs.